A duplication of the Anti-Müllerian hormone gene is associated with genetic sex determination of different Oreochromis niloticus strains - Curzon, A. Y. (Heredity (Edinb), 2020)
Sex determination (SD) mechanisms are ancient and conserved, yet much diversity is exhibited in primary sex-determining signals that trigger male or female development. In O. niloticus, SD is associated with a male-specific locus on linkage group (LG) 23 which harbors the Y-linked Anti-Müllerian hormone (amh) gene, and a truncated duplication, denoted amhΔy. We have evaluated the possible role of identified indels and SNPs in the amh gene on SD, based on conservation in different O. niloticus strains. A fluorescent assay for the detection of a 5 bp insertion in amhΔy exon VI, efficiently discriminated between XX, XY, and YY genotypes. Concordance rate between amhΔy and sex varied in six Oreochromis strains, from 100% (Ghana) through 90% (Swansea) to 85% (Thai-Chitralada). The association of amhΔy with sex was found to be conserved in all tested O. niloticus strains, and thus supports its key role in SD. However, the previously identified missense SNP (C/T) in amh exon II was found only in the Swansea strain, thus excluding its candidacy for the causal variation of SD across all strains. Effects of markers on LGs 1, 3, and 23 (amhΔy) fully explained sex distribution in one Thai-Chitralada family (R(2) = 1.0), whereas in another family only the major effect of LG23 (amhΔy) was significant (R(2) = 0.37). Thus, amhΔy on LG23 is associated with genetic SD, either as a single causal gene in different O. niloticus strains, or in combination with segregating genes on LGs 1 and 3 in the Thai-Chitralada hybrid strain.